محاضرات حول: أعلام الفكر السياسي وا إلصلاحي في الوطن العربي - خليفي, عبد القادر (جامعة محمد بوضياف بالمسيلة كلية العلوم الانسانية والاجتماعية, 2024)
تتناول هذه المطبوعة مختلف الأفكار والأطروحات التي قدمها جملة من الرواد مشرقا ومغربا على امتداد القرن التاسع عشر والنصف الأول من القرن العشرين، للنهوض بالإنسان العربي من حالة الركود والجمود والتخلف الحضاري التي عمرت لعدة قرون قصد اللحاق بالركب العالمي، وهي الأفكار التي تميزت بالثراء بما يعكس تنوع المشارب والأيديولوجيات التي استقى منها المنظرون والمصلحون برامجهم لإحداث التغيير المأمول. وبالنظر إلى الواقع العربي المتباين من مكان إلى آخر تاريخيا وسياسيا وثقافيا واجتماعيا، فقد عولجت مسألة النهضة وفق رؤى سلفية محافظة رأت في العصر الذهبي للإسلام المرجع الوحيد للبناء، ورفضت التعاطي مع الأفكار الحداثية القادمة من أوربا والغرب عموما، ورؤى علمانية ليبيرالية، اعتبرت منجزات الحضارة الغربية الحديثة هي الخلاص لتخلف العرب والمسلمين، وطالبت بالقطيعة التامة مع الماضي، في حين جنح تيار ثالث إلى التوفيق بين النموذجين. This publication deals with the various ideas and theses presented by a number of pioneers from the East and West throughout the nineteenth century and the first half of the twentieth century, to advance the Arab human being from the state of stagnation, stagnation, and cultural backwardness that has lasted for centuries in order to catch up with the global movement. These ideas were characterized by their richness, which reflects the diversity of... The stripes and ideologies from which theorists and reformers derived their programs to bring about the desired change. In view of the different Arab reality from one place to another historically, politically, culturally and socially, the issue of the Renaissance was addressed according to conservative Salafist visions that saw the Golden Age of Islam as the only reference for construction, and refused to deal with modernist ideas coming from Europe and the West in general, and liberal secular visions that were considered the achievements of Western civilization. Modernism is the salvation for the backwardness of Arabs and Muslims, and demanded a complete break with the past, while a third movement tended to reconcile the two models.
Keywords: Pedagogical handout for first-year Masters students History of the Contemporary Arab World Prepared by Dr. Khelifi Abdelkader النهضة العربية – الحملة النابليونية – تيار الأصالة – الحركات الإصلاحية – الوهابية – القومية العربية – السلفية - البعثات العلمية – الطهطاوي – خير الدين التونسي – الكواكبي – الإرساليات التبشيرية التيار التوفيقي – حركة الترجمة – الاستشراق